Inheritance and molecular mapping of the genomic regions governing seed viability in soybean (Glycine max. L. Merr.): Inheritance and molecular mapping of the genomic regions governing seed viability in soybean (Glycine max. L. Merr.) - MANISHA SAINI; RAJU R YADAV; RAHUL KUMAR; MANU YADAV; N KRISHAN KUMAR RATHOD; MENIARI TAKU; SUDIPTA BASU; R AMBIKA RAJENDRAN; SK LAL; AKSHAY TALUKDAR (Journal of Oilseeds Research, 2023)
Loos of seed viability in soybean (Glycine max L. Merrill, 2n=40) during ambient storage from harvest to the next planting season is a significant barrier for the production of high-quality seeds. The present study includes the inheritance and molecular mapping of the loci linked to seed viability in soybean. For this, five high viable genotypes (>90% germination after one year of storage) viz. EC-1023, EC-105790, G2651, UPSL34, UPSL736 and three poorly viable genotype (<70% germination after one year of storage) viz. MACS-565, PK1243, VLS61 were hybridized in all possible combination. Obtained F1 were advanced separately. Cross EC1023 x VLS61 and their derived F2:3 seeds, were exposed to 72 hours of accelerated ageing (AA) at 41°C and 100% RH, followed by a germination. After AA test, germination % of EC1023 and VL5-61 were 40 and 14, respectively, whereas range of F2:3 seeds were 4.16 to 71.42 %. The seed viability is governed by polygenes or quantitative trait loci (QTL), as evidenced by the continuous distribution of germination % of F2:3 seeds. Parental polymorphism was studied with 506 SSR markers indicated it to 20.35% whereas distribution of the polymorphism was not uniform across the chromosomes; Chr. 15 had 46.15% polymorphism as against 15.78% on Chr. 3 and 4. Through inclusive composite interval mapping 8 QTL for seed viability on Chr. 6, 7, 8, 10, 13 and 17, respectively, were mapped. Two of the eight QTLs appear to be major QTLs, as their PVE percent is greater than 10% and other seems as minor ones. Previously reported markers linked to seed viability were also validated in the parental genotypes, with only Satt538 being able to differentiate the five good and three poor storing genotypes. The genetics of seed viability, as well as the QTLs and markers found in this study, will pave the way for molecular breeding to generate genotypes with improved seed viability.